2012
DOI: 10.1590/s0102-67202012000400008
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre o estado nutricional de vitamina a e a regressão da esteatose hepática após gastroplastia em Y- de- Roux para tratamento da obesidade classe III

Abstract: -Background -Vitamin A participates in several essentials functions in the human body and their serum concentrations may be decreased in non-transmissible diseases. Aim -To assess the relationship of the nutritional status of Vitamin A through the serum concentrations of retinol and beta carotene, with regression of hepatic steatosis in individuals who undergone Roux-en-Y gastric bypass surgery for treatment of class III obesity. Methods -Were included 30 individuals, male and female, submitted to Roux-en-Y ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Hepatic steatosis, identified by elevated levels of AST, ALT, GGT and biopsy specimens, also showed reduction after bariatric surgery. Other authors also observed a 46.6% reduction in steatosis among the individuals studied [24][25][26][27] . A meta-analysis carried out in the United Kingdom indicated a reduction of liver enzymes, considered markers of liver function and liver damage, statistically associated with the reduction of hepatic steatosis shortly after surgery 25 .…”
Section: Discussionmentioning
confidence: 66%
“…Hepatic steatosis, identified by elevated levels of AST, ALT, GGT and biopsy specimens, also showed reduction after bariatric surgery. Other authors also observed a 46.6% reduction in steatosis among the individuals studied [24][25][26][27] . A meta-analysis carried out in the United Kingdom indicated a reduction of liver enzymes, considered markers of liver function and liver damage, statistically associated with the reduction of hepatic steatosis shortly after surgery 25 .…”
Section: Discussionmentioning
confidence: 66%
“…Vitamin A is an essential micronutrient in several physiological processes in the human body, being necessary for the adequate functioning of the immune system, visual acuity, cell proliferation/differentiation, and gene expression. 1 , 2 , 3 , 4 Despite universal susceptibility, its deficiency is more frequent in children under five years, pregnant women, and lactating women, which is why these groups are considered biologically more vulnerable to this nutritional deficiency. 5…”
Section: Introductionmentioning
confidence: 99%
“…It is noticeable that there are not many publications in the literature discussing the association between nutritional disorders and quality of life with weight loss 5 , 8 , 21 . So, this study aims to investigate the nutritional disorders in patients submitted to bariatric surgeries and its connections with weight loss and quality of life.…”
Section: Introductionmentioning
confidence: 99%